Prevalence and antibiotic resistance of Salmonella enterica in poultry and raw meat in the Can Tho province, Vietnam - Nilsson, Oskar (2009)
The aim of this study was to get an overview of prevalence and resistance patterns of Salmonella enterica in chicken as well as antibiotic use and knowledge of antibiotic resistance among farmers in the Can Tho region, Vietnam. Material was sampled on local farms and markets during six weeks in October to November of 2008. Twelve markets were selected and each market was sampled once for a total of 96 samples of neck skin of chicken. In addition 20 farms were selected and rectal swabs were collected on a total of 96 chickens. Analyses of market samples were based on the principles of the Nordic Committee on Food Analysis but adapted to local practises. The sampling from farms was based on procedures used in humans and studies of other bacteria in chicken, thus being more uncertain in its outcome. A total of 11 samples, nine from farms and two from markets, were positive or uncertain on polyvalent antiserum testing and hence sent to Sweden for final confirmation and serotyping. Surprisingly only one out of the eleven isolates was shown to belong to the Salmonella enterica species, namely S. Enteritidis. The reason to the large number of negative samples has to be contributed to the inexperience of myself as well as to the use of modified methods in a foreign laboratory environment. The positive sample was tested for antibiotic resistance showing resistance to four different antibiotics; ampicillin, streptomycin, sulfamethoxazol and tetracyclin. Farmer awareness was studied through a questionnaire and showed low knowledge of antibiotic resistance development and moreover that antibiotics are used as a prophylactic and dependent on availability rather than in regard to its effect on specific disease causing agents.